The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1346/ccmn.1979.0270506
|View full text |Cite
|
Sign up to set email alerts
|

Biotite Alteration in Deeply Weathered Granite. II. The Oriented Growth of Secondary Minerals

Abstract: Abstract--Single grain X-ray and electron diffraction patterns of weathered biotite flakes exhibit groupings of 001 and hk reflections of biotite, vermiculite, mixed-layer clay minerals, and kaolinite indicating that the secondary minerals are in parallel crystallographic orientation to the parent biotite. Asterism of biotite reflections is enhanced by weathering. Gibbsite crystals developed in parallel basal orientation to biotite flakes. Most goethite in weathered biotite occurs as aggregates of randomly ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…(Keller, 1978). Many studies of the weathering of biotite and muscovite have reported the oriented growth of kaolinite to form pseudomorphs (Gilkes and Suddhiprakarn, 1979;Ahn and Peacor, 1987;Eggleton, 1988, 1990). The bundles of tubes ( Figure 4A) show clear boundaries and appear to be more densely packed than halloysite masses that are considered to have crystallized from solution (Keller, 1978;Banfield and Eggleton, 1990).…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…(Keller, 1978). Many studies of the weathering of biotite and muscovite have reported the oriented growth of kaolinite to form pseudomorphs (Gilkes and Suddhiprakarn, 1979;Ahn and Peacor, 1987;Eggleton, 1988, 1990). The bundles of tubes ( Figure 4A) show clear boundaries and appear to be more densely packed than halloysite masses that are considered to have crystallized from solution (Keller, 1978;Banfield and Eggleton, 1990).…”
Section: Morphologymentioning
confidence: 99%
“…Halloysite tubes crystallized from solution can also achieve some degree of parallel orientation (Keller, 1978), but they mostly radiate outwards from the substrate and are less densely packed. Micas exhibit a perfect cleavage along (001) and commonly exfoliate along this plane in the initial stages of weathering thereby creating an array of parallel slits (Gilkes and Suddhiprakarn, 1979). Such parallel slits provide an environment that would generate a planar (two dimensional) mat of halloysite tubes but would not lead to a high degree of orientation of tubes in three dimensions.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a very weak ring pattern for kaolinite in Figure 1B, which indicates that although the majority of the kaolinite crystals are in parallel orientation, some kaolinite crystals, or possibly halloysite crystals, are distributed at random orientations about the c'axis. A similar, highly-oriented growth of secondary clay minerals in weathered biotite extending from micrometer to millimeter scale was observed by Gilkes and Suddhiprakarn (1979). Oriented secondary minerals develop if the parent and secondary minerals contain similar structural units (groups, chains, sheets), and the parent mineral contains adequate amounts of elements of a residual nature (Gilkes et al, 1986).…”
Section: Mineralogy Of the Single Flakesmentioning
confidence: 65%
“…Weathering of mica in soils has been investigated by many workers, with most research being directed towards biotite (Meunier and Velde, 1979;Gilkes and Suddhiprakarn, 1979;Ahn and Peacor, 1987;Banfield and Eggleton, 1988). In contrast, weathering of muscovite, which is a common constituent of soils, has received relatively little attention (Banfield and Eggleton, 1990).…”
Section: Introductionmentioning
confidence: 99%